The analyst, the transference, and the representational world - Kaplan, Stanley M. (Comprehensive psychiatry, 1976)
Viewing the phenomenon of transference within the metapsychological context of the representational world, and the shapes of the important past and present object representations in it, has a clarifying value. Any new approach to what Freud characterized as “the almost inexhaustible topic of transference” 1 is justified because of the central position it holds in the analytic treatment process. The basic idea presented in this paper is that transference can be viewed in terms of the changing shapes of the object representation of the analyst as he is formed and transformed in the representational world during the course of the analysis. These changes are affected by the regression during analysis, the influences of the patient's important past object and self representations which are laid down in his representational world (particularly in the unconscious part of it), the interventions of the analyst, and other occurrences during the course of the analysis. The term “transference” has been defined in a variety of ways. I will use the definition of Sandler et al. 2—“a special illusion which develops in regard to the other person, one which, unbeknown to the subject, represents, in some of its features, a repetition of a relationship towards an important figure in the person's past … this is felt by the subject, not as a repetition of the past, but as strictly appropriate to the present and to the particular person involved.” The term transference has also been described in terms of the transference neurosis, the externalization of the superego, projections of the id or aspects of the patient's own self-representation onto the analyst, “character” transferences, the “basic” or “primary” transference of the working alliance, “ready-made” transferences, acting-out of transference, and so on. Some of these will be dealt with in this paper.